Silat Learning Profile (Case Study at Silek Sarasah Marapi College in XII Kampung Nagari Canduang Koto Laweh) - Noverwan, Aldy; Solfema, Solfema (Universitas Negeri Padang, 2023)
This research is motivated by the phenomenon of the uniqueness of the establishment of the Tuo Sarasah Marapi martial arts college in XII Nagari Canduang Koto Laweh village, which has the principle of adab higher than science. This research aims to find out how Sarasah Marapi silat as a community unifier in learning silat to Sarasah Marapi silat trainees. This research approach is qualitative with a type of case study research that uses data collection techniques by means of observation, interviews and documentation after which it is analyzed using triangulation. The results of this study are 1) History of the Establishment of Silat Sarasah Marapi College. 2) People's View on Sarasah Marapi Silat School. 3) Aspects of Preserving Traditional Silat Sarasah Marapi and 4) Community Support for Sarasah Marapi Silat School.